2015
DOI: 10.1089/acm.2013.0466
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Regular Sauna Bathing for Chronic Tension-Type Headache: A Randomized Controlled Study

Abstract: Regular sauna bathing is a simple, self-directed treatment that is effective for reducing headache pain intensity in CTTH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 28 publications
0
32
0
1
Order By: Relevance
“…25,26 Having sauna baths also improves headache disorders. In an RCT by Kanji et al, 27 37 people with chronic tension-type headache were randomized to regular sauna bathing or advice and education for a period of 8 weeks, and sauna therapy was found to substantially improve headache intensity. Although there is some evidence from a Japanese study that thermal therapy improved the symptoms of patients with mild depression, 28 to our knowledge, no study has as yet reported the effects of Finnish sauna bathing on depression.…”
Section: Pulmonary Diseasementioning
confidence: 99%
“…25,26 Having sauna baths also improves headache disorders. In an RCT by Kanji et al, 27 37 people with chronic tension-type headache were randomized to regular sauna bathing or advice and education for a period of 8 weeks, and sauna therapy was found to substantially improve headache intensity. Although there is some evidence from a Japanese study that thermal therapy improved the symptoms of patients with mild depression, 28 to our knowledge, no study has as yet reported the effects of Finnish sauna bathing on depression.…”
Section: Pulmonary Diseasementioning
confidence: 99%
“…Sauna bathing is now emerging as an activity which may have therapeutic potential for adverse health outcomes. Sauna bathing has been used for the treatment and improvement of symptoms associated with several acute and chronic conditions such as rheumatic disease, 59 headache, 15 and skin diseases. 60 Sauna bathing has also been recently reported to have protective effects on the long-term risk of CVD and non-CVD.…”
Section: Implications Of Findingsmentioning
confidence: 99%
“…9 Sauna bathing, a traditional Finnish activity which is commonly used for the purposes of pleasure, relaxation, and wellness, and becoming a popular activity in many other countries, 12,13 has been observed to be linked to several health benefits. These include improvement in the pain and symptoms associated with musculoskeletal diseases 14 ; treatment of chronic headache 15 ; improvement in CV function 16,17 and reduced risk of respiratory diseases, 18,19 hypertension, 20 and neurocognitive disease. 21 Recent long-term observational epidemiological evidence has shown that having frequent sauna baths is independently associated with a reduced risk of SCD.…”
mentioning
confidence: 99%
“…The use of sauna is increasingly becoming common in many other countries. (1) Sauna bathing has been linked with many health benefits and these include improvement in the pain and symptoms associated with musculoskeletal diseases;(2) treatment of chronic headache; (3) and amelioration of skin diseases such as psoriasis and urticaria. (4) Recent emerging evidence also suggests that sauna bathing is associated with lowered risks of cardiovascular disease (CVD), (5) neurocognitive disease, (6) and all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%